THE ROLE OF BORIBOY AHMEDOV RESEARCH IN TEMURID STATE IN CENTRAL ASIA - Rahm Onberdiev Feruz (Journal Park Publishing, 2023)
The article tried to reveal the place of research of Academician of the Academy of Sciences of Uzbekistan, honored scientist, historian and Orientalist, doctor of historical sciences Bo'riboy Ahmedov (1924-2002) in the study of the history of Amir Temur and the Timurid state.
Keywords: Amir Temur, timurians, history, Bo'riboy Ahmedov, studies, works, historical novels.